Alterations of CCR2 and CX3CR1 on Three Monocyte Subsets During HIV-1/Treponema pallidum Coinfection - Guo, Na; Chen, Yongchang; Su, Bin; Yang, Xiaodong; Zhang, Qiuyue; Song, Ting; Wu, Hao; Liu, Cuie; Liu, Lifeng; Zhang, Tong (Frontiers in Medicine, 2020)
HIV-1/Treponema pallidum (T. pallidum) coinfection has become a global challenge, and three monocyte subsets express varying levels of the chemokine receptors CCR2 and CX3CR1. We recently evaluated the association between monocyte subsets and regulatory T cells in HIV-infected individuals with syphilis. Currently, the dynamic changes of CCR2 and CX3CR1 on monocyte subsets during HIV-1 and syphilis coinfection have not been fully investigated. In this study, cell surface staining was used to explore CCR2 and CX3CR1 expression on three monocyte subsets during HIV-1/T. pallidum coinfection. We found that CCR2 densities on the classical monocyte subsets decreased in acute HIV-1 infected (AHI) patients, chronic HIV-1-infected individuals without antiviral therapy (ART) (CHI+ART-), chronic HIV-1-infected individuals receiving ART (CHI+ART+), rapid plasma reagin-positive (RPR+) individuals, CHI+ART- plus RPR+ (CHI+RPR+ART-) individuals, and CHI+ART+ plus RPR+ (CHI+RPR+ART+) individuals. CX3CR1 density increased on the three monocyte subsets during HIV-1 and/or T. pallidum infection. CX3CR1 density on the intermediate and nonclassical monocyte subsets in CHI+ART- individuals was lower than that in CHI+ART+ individuals, and CX3CR1 density on the three monocyte subsets in CHI+ART+ individuals was higher than that in CHI+RPR+ART+ individuals. Our data provide new insight into the roles of CCR2 and CX3CR1 on three monocyte subsets in HIV-1 and T. pallidum pathogenesis.